A fast screening method for tricyclic antidepressants and their urinary metabolites by FAB-tandem mass spectrometry. Issue 3 (1997) - Schäfer Schäfer, M. M.; Budzikiewicz Budzikiewicz, H. H.; Brzezinka Brzezinka, H. H.; Schifferdecker Schifferdecker, M. M.
Abstract : A screening method for tricyclic antidepressants (TCA) and their urinary metabolites by FAB tandem mass spectrometry (FAB MS/MS) is presented. The collision induced dissociation (CID) behavior of pure dibenzocycloheptadienes (amitriptyline1, nortriptyline2 ), dibenzoxepines (doxepine3, dosulepine4 ), dibenzazepines (imipramine5, desipramine6, trimipramine7 ) and the iminostilbene derivative opipramol8 is described and used for the specific determination of these tricyclics by MS/MS. For the screening procedure a methanolic extract of the urine sample is passed through a XAD-2 column and the eluate is examined without further purification after evaporation of the solvent. Identification of the TCA is achieved by constant neutral loss (CNL) scans for 173 u, 195 u and 193 u and subsequent daughter ion spectra of the molecular ions [M+H] + . Glucuronide conjugate metabolites of the tricyclic antidepressants1, 2, 3, 6, 8 could be identified by CNL-scans (176 u) and the assignments were confirmed by daughter ion mass spectra. A urine sample of a fatal1, 2, 8 overdose and samples of three patients under therapeutic dosage with1, 3 or6 are presented as examples for application.